Application of botulinum toxin for optimizing the harmony of gummy smile. Case report and literature review - Gregnanin Pedron, Irineu (2017)
The botulinum toxin (BT) is a protein of bacterial origin that causes temporary weakening of the muscular activity. In dentistry, it has been indicated to treat certain muscle disorders such as temporomandibular disorders, orofacial dystonia, and bruxism; however, it is still little used in dental aesthetic procedures. The objective of this work is to present the case of a patient with gingival smile that was treated with the application of BT, avoiding surgical resective procedures. After applying local anesthesia, two units of botulinum toxin type A was injected in the lateral region to each nostril of the patient. The BT application caused uniform dehiscence of the upper lip, reducing gingival exposure and achieving satisfactory results for the patient. We concluded that botulinum toxin type A is a non-invasive, fast, safe and effective therapeutic option that produces harmonic results, that produces harmonic results. It may be considered by the dentist as an alternative to the correction, completion or complementation of aesthetic procedures, increasing the quality of life and the self-esteem of patients.